The Influence Of External Locus Of Control, Professional Commitment, Complexity Of Tasks On Moral Reasoning And Dysfunctional Audit Behavior (Case Study Of Auditors In The Public Accounting Office Of Surabaya City) - Tarenza Noviandari; Tri Ratnawati; Nursaadatun Nisak Ahmad (Cita konsultindo, 2024)
This research was conducted with the aim of finding out whether moral reasoning as mediation can influence dysfunctional audit behavior. The research was conducted at a Public Accounting Firm in the City of Surabaya, with a sample of 60 auditors. Hypothesis testing in research uses the SmartPLS 3.0 application with outer model and inner model testing. The research results show that moral reasoning has a significant effect on dysfunctional audit behavior. This shows that with moral reasoning, auditors must be careful in taking action and making decisions to prevent dysfunctional audit behavior. Dysfunctional audit behavior can occur due to fraud or behavior that deviates from audit standards carried out by an auditor in carrying out audit tasks.